(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Present study was undertaken to investigate the relative efficacy of four growth regulators, viz., α-naphthalene acetic acid (NAA), indole-3-acetic acid (IAA), gibberellic acid (GA) and 2,4-Dichlorophenoxy acetic acid (2,4-D) at various concentrations (ppm) on the yield and some other quality characteristics of grape (Zakkao cultivar) at the experimental grape research vine of BCSIR Laboratories, Rajshahi during the period January, 2003 to July, 2004. Yield was found to be increased (33.11 %) by spraying with 05 ppm of 2,4-D as compared to control and other growth regulator treatments. Fruits of treated plants showed increased total soluble solids (20.28 %) and vitamin (23.18 %) than that of untreated one. The titrable acidity (T. A) of fruits (33.01 %) of the treated plants was reduced significantly as compared to control. Bangladesh J. Sci. Ind. Res. 42(1), 59-66, 2007